O universo e as estrelas em literaturas infantil e juvenil: caminhos discursivos das literaturas negro-brasileira e indígena - Souza, Gustavo Tanus Cesário de (2023)
The ethnic-racial groups that formed Brazil have always been represented in literature, having been, at first time, characters in narratives, as antagonists, in sixteenth-century texts, to the narratives that formed the idea of nation, and more recently, as protagonists, however, in most of these texts, they are represented with stereotypes. These constructions contributed to the continuity of images that make up a negative imagery about subjects and the so-called “minority” cultures. This change began through the literature written by the subjects of cultures, in which there is a noticeable change in the way of representing themselves, communities, their cultures, epistemes, especially in Indigenous and Black-Brazilian literary productions for children and young people. The aim is to undertake reflections on children's and youth literature by Black and Indigenous authors, through literary texts, analyzing convergences in their aesthetic, political and literary proposals, realizing how they elaborate the idea of literature, ways of being in the world, modes of representation of their cultures, epistemes, seeking an understanding of their specific literary fields. For the understanding of children's literature, we mobilized the founding texts, based on Leonardo Arroyo (1968, 1988), followed by the works of Regina Zilberman (1981, 1982, this one with Lígia Cademartori, 1984, 1986 and 2005), Nelly Coelho (1981, 1983, 1985), Marisa Lajolo (1982, 1986, the latter co-authored by Zilberman), Maria Antonieta Cunha (1985), among others. In relation to Black-Brazilian and Indigenous literature, we used to work that dealt with the constitution of these literatures, and understand of them as systems in their historical, theoretical, and critical dimensions. For the first literature, discussions done by Eduardo de Assis Duarte, Cuti, Conceição Evaristo, Maria Nazareth Fonseca, Florentina de Souza, Inaldete Pinheiro de Andrade, Ione Jovino, among others, were considered, and for the second literature, authors such as Graça Graúna, Daniel Munduruku, Maria Inês de Almeida, Julie Dorrico, among others. This theoretical research started from a bibliographic path to the presentation of a corpus of children's and youth literature by Black and Indigenous authors, mobilized for reading and discussion, with a view to discursive paths about literature. To do so, we mobilized the methodological-operative concept of “constellation”, built via Benjamin, Adorno, Krenak, Munduruku, Hitxa Pataxó, Esmeralda Ribeiro, Marcos Fabrício Lopes da Silva, Ryane Leão and our understandings; metaphor whose comprehension have the potential to redesign what is posited as literary coming of age. In the various dimensions of use, figured in the intentional categories, we used to elaborate dimensions in analyzes of these literary texts, to observe the politics of literature in the relations, namely: Policies, authorship and literary system; Illustration as a form of authorship; Literary genres, in prose; Animals we are; Readings of imagined, imaginary worlds and so many images; Ancestry, present action of respect for people and time; and Mediator, narrator / Griô, Nganga, Pajé, or the oldest, in the movements of the wheel of time. It also presents a discussion about “eventual authorship”, “addressing”, “choice of reception”, “mediated re-addressing”, “counter-imagings” and “re-imagings”, “affective communities”, movements that they demonstrate, from a playful reading, the powers of the Black-Brazilian and Indigenous children's and youth literary fields, as their particularities in the face of the general field.